Production and Characterization of IgY against Canine IgG: Prospect of a New Tool for the Immunodiagnostic of Canine Diseases - Santos,Fernanda Nunes (2014)
This study describes the production of a new avian polyclonal antibody (IgY) against canine IgG, as another tool for the immunodiagnostic using IgY technology. The immunization protocol caused neither deaths nor pathologies, and no decline in egg laying capacity was detected. The total concentration of isolated IgY was constant, without significant difference (p> 0.05), with average of 97.55 mg of IgY/yolk. The IgY revealed a strong sensitivity and specificity in recognition against canine IgG by ELISA. After the immunization, there was a significant increase in the production of IgY specific from the first to the second month (p <0.05), reaching a stable peak without decrease in the production by the end of the analysis period (p > 0.05). The IgY demonstrated a suitable specificity in Western blot against the purified and serum canine IgG, not enabling recognition of canine IgM or IgG of other animal species. The specific IgY in the egg yolks of immunized hens proved to be a molecule with an appropriate purity and desired specificity against the immunizing antigen. Moreover, its constant production in large quantities during the four months analyzed indicated that IgY antibody production technology could be considered as an excellent alternative to the standard methods.